ChemInform Abstract: Ruthenium‐Catalyzed Hydrocarboxylation of Internal Alkynes. Issue 30 (7th July 2016) - Jeschke, Janine; Engelhardt, Tony B.; Lang, Heinrich
Abstract: The reaction of benzoic acids and alkynes proceeds with excellent E/Z‐selectivity furnishing the E‐isomers of the respective alkenylbenzoates only.